THE IMPACT OF THE FLIPPED CLASSROOM MODEL ON STUDENT ENGAGEMENT AND ACADEMIC ACHIEVEMENT: A SYSTEMATIC REVIEW OF THE LITERATURE - Adhe Risky Mayasari; Mujahidin (Adisam Publisher, 2025)
This study aims to explore the impact of the flipped classroom model on student engagement and academic achievement through a systematic literature review. The flipped classroom model, which requires students to study materials independently outside of class and use class time for interactive activities, has become a much- discussed pedagogical innovation. Through the analysis of various relevant studies, the findings of this research show that flipped classroom significantly increases students' engagement in the learning process and has a positive impact on their academic achievement. Students feel more motivated and prepared to join class discussions, understand the material more deeply, and show improvements in academic outcomes. This conclusion highlights the importance of implementing the flipped classroom model as an effective strategy in improving education quality and student learning performance.